2020
DOI: 10.15252/msb.20199367
|View full text |Cite
|
Sign up to set email alerts
|

Pan‐tissue analysis of allelic alternative polyadenylation suggests widespread functional regulation

Abstract: Alternative polyadenylation (APA) is a major layer of gene regulation. However, it has recently been argued that most APA represents molecular noise. To clarify their functional relevance and evolution, we quantified allele-specific APA patterns in multiple tissues from an F1 hybrid mouse. We found a clearly negative correlation between gene expression and APA diversity for the 2,866 genes (24.9%) with a dominant polyadenylation site (PAS) usage above or equal to 90%, suggesting that their other PASs represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Of the 2,443 events, only 85 (3.5%) events exhibited opposite signs of ΔPSI T in the two tissues, fitting scenario 1. This shows that cis -divergence causing opposite allelic changes between tissues is rare, similar to the previously observed patterns for alternative polyadenylation ( Li et al, 2020 ). Among the remaining events, 247 fit scenario 2 with parallel changes in isoform abundance between tissues and 456 fit scenario 4 with equal divergence across tissues, whereas the majority (1,655, 67.7%) fit scenario 3 with only one allele showing tissue-dependent splicing.…”
Section: Resultssupporting
confidence: 88%
“…Of the 2,443 events, only 85 (3.5%) events exhibited opposite signs of ΔPSI T in the two tissues, fitting scenario 1. This shows that cis -divergence causing opposite allelic changes between tissues is rare, similar to the previously observed patterns for alternative polyadenylation ( Li et al, 2020 ). Among the remaining events, 247 fit scenario 2 with parallel changes in isoform abundance between tissues and 456 fit scenario 4 with equal divergence across tissues, whereas the majority (1,655, 67.7%) fit scenario 3 with only one allele showing tissue-dependent splicing.…”
Section: Resultssupporting
confidence: 88%
“…APAs likely play a role in many processes involved in gene expression, including nuclear export, localization, stability, degradation, repression, translation, and protein diversification [104]. Additionally, APAs associated with differentiation, proliferation, and tissue-specific expression have been reported [105]. APAs at the gene-level can be discovered using EST, microarray, RNA-Seq, 3' RNA-Seq, and qRT-PCR methodologies.…”
Section: Alternative Polyadenylation (Apa) Site Usagementioning
confidence: 99%
“…Nevertheless, several studies have been pointing out that these capsules may cause unwanted fibrotic reactions. [150] As a result, new formulations have been envisaged for cell encap sulation including alginatechitosan microcapsules [151] and decellularized liver matrixalginate gel beads. [148] Experiments using comicroencapsulated hepatocytes and HUVECs, trans planted intraperitoneally into rat models of fulminant hepatic failure (FHF), showed that hepatocytespecific functions were significantly better than the transplant of isolated hepatocytes or even microcapsules with hepatocytes only.…”
Section: D Culturingmentioning
confidence: 99%